A comparative study of supraclavicular versus infraclavicular approach for central venous catheterization in neurosurgical patients - Anjum, Shazia; Singh, Sarbjit; Ali, Zulfiqar; Ubaid, Sheikh; Majid, Syed; Imtiyaz, Syed Yusra (International Journal of Research in Medical Sciences, 2019)
Background: Central venous cannulation is a commonly performed procedure in neurosurgical patients to maintain the hemodynamic stability in the intraoperative period. It is used for infusion of intravenous fluids, vasopressors central venous pressure monitoring and detection of air embolism. Subclavian vein is commonly performed as there are minimal effects of positioning on it. Supraclavicular approach to subclavian vein cannulation is not as frequently employed as the infraclavicular approach. The purpose of this study was to compare the supraclavicular approach versus the infraclavicular approach in terms of number of attempts, success rate of catheterization and complications associated with the procedure. Methods: About 150 patients undergoing various neurosurgical procedures were enrolled in the study. They were divided into two groups. 75 patients underwent right supraclavicular catheterization of subclavian vein while as 75 patients underwent right infraclavicular catheterisation of the subclavian vein. The number of attempts for cannulation, success or failure of catheterization and any complications associated with the procedure or in the postoperative period were noted in each group. The data was compared between the two groups by using Chi-square test and Student’s Independent Samples T-test. Results: The right supraclavicular vein was successfully cannulated in 90.66% while as the right infraclaviclar vein was successfully cannulated in 96% of the patients (p >0.05). Malpositioning of catheter (threaded in contralateral subclavian) was noted in 4 patients in Group S and ipsilateral internal jugular vein in 2 patients. Pneumothorax was encountered in 1 patient in the group S undergoing supraclavicular subclavian vein cannulations while as subclavian arterial puncture was seen in 4 patients who underwent infraclavicular arterial puncture. Conclusions: There was no difference in successive cannulations between right the supraclavicular and right infraclaviclar veins. The rate of complications between the two approaches was comparable.